2018
DOI: 10.1523/eneuro.0244-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

The Variability of Neural Responses to Naturalistic Videos Change with Age and Sex

Abstract: Neural development is generally marked by an increase in the efficiency and diversity of neural processes. In a large sample (n = 114) of human children and adults with ages ranging from 5 to 44 yr, we investigated the neural responses to naturalistic video stimuli. Videos from both real-life classroom settings and Hollywood feature films were used to probe different aspects of attention and engagement. For all stimuli, older ages were marked by more variable neural responses. Variability was assessed by the i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 59 publications
8
46
1
Order By: Relevance
“…Indeed, our data appear to support this latter accountolder individuals showed less temporal variability on a trial-by-trial basis than younger individuals in certain regions, consistent with prior developmental findings in other domains (Koolschijn et al, 2011;Ordaz et al, 2013). Our findings might also be explained by prior work showing that age-related trajectories of temporal variability in the brain do not follow a single pattern, but instead show regionally-specific increases and decreases in variability (Nomi et al, 2017;Petroni et al, 2018). This supports the notion that development is possibly characterized by a process of 'variability tuning', where an intermediate amount of variability is necessary for the execution of psychological tasks, but what is classified as "intermediate" varies across brain regions.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, our data appear to support this latter accountolder individuals showed less temporal variability on a trial-by-trial basis than younger individuals in certain regions, consistent with prior developmental findings in other domains (Koolschijn et al, 2011;Ordaz et al, 2013). Our findings might also be explained by prior work showing that age-related trajectories of temporal variability in the brain do not follow a single pattern, but instead show regionally-specific increases and decreases in variability (Nomi et al, 2017;Petroni et al, 2018). This supports the notion that development is possibly characterized by a process of 'variability tuning', where an intermediate amount of variability is necessary for the execution of psychological tasks, but what is classified as "intermediate" varies across brain regions.…”
Section: Discussionsupporting
confidence: 91%
“…By using interspecies functional correlation analysis in conjunction with a naturalistic visual stimulus, Mantini and colleagues (2012) were able to identify functional homologies across primate species without assuming anatomical correspondence. The same logic can be used to compare neural entrainment to a naturalistic stimulus across populations, such as between autistic patients and controls (Hasson et al, 2009;Salmi et al, 2014) or over the course of development (Cantlon and Li, 2013;Campbell et al, 2015;Petroni et al, 2018;Piazza et al, 2018).…”
Section: Applications Of Isc Analysismentioning
confidence: 99%
“…Studies of neural similarity during child development are also emerging. When studying between-subject measures of EEG signal during naturalistic viewing, Petroni et al showed that intersubject correlations (ISCs) of evoked-responses in participants ages 5-44 years decreased with age, and also, that males generally had lower ISCs relative to females (Petroni et al, 2018). In other words, neural variability across subjects in these longer time courses decreased with age.…”
Section: Connectome Stability and Similarity As Developmental Measuresmentioning
confidence: 99%